Pruritus: Management Algorithms and Experimental Therapies - Steinhoff, Martin (2011)
Pruritus (itch) is a major symptom in many dermatologic as well as systemic diseases and has a dramatic impact on the quality of life in these patients. The symptom of itch has to be treated on the basis of its pathophysiology and its underlying disease. In daily practice, a “quick” diagnosis of the underlying disease is often difficult, although a rapid relief of the itch is desired. We often treat patients on the basis of the symptomatology. A rational therapeutic ladder for a symptomatic therapy is useful until the final diagnosis has been confirmed. There are probably many subtypes of pruritus, just as there are many diseases that cause itch. The pathophysiology in many subtypes of pruritus is still poorly understood, hindering a rapid and targeted treatment strategy. An extensive diagnostic workup is often required to determine the final cause(s) of the itch. Thus, in daily life, physicians often start with a more or less rational therapeutic strategy to combat the debilitating itch. We present possible therapeutic ladders that form the basis for effective therapeutic itch strategies in various diseases. On the basis of our current knowledge about the different pathophysiologies of itch, on clinical trials or case reports, and our own clinical experience, we aim to present therapeutic ladders for the rapid as well as long-term management of itch. Finally, we summarize current exciting developments of experimental strategies in itch research and in clinical development for itch therapy.